2020
DOI: 10.1007/s13364-020-00494-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human land use and landscape productivity on population dynamics of red fox in southeastern Norway

Abstract: In the boreal forest, the red fox (Vulpes vulpes) is a key species due to its many strong food web linkages and its exploitation of niches that form in the wake of human activities. Recent altitudinal range expansion and a perceived population increase have become topics of concern in Scandinavia, primarily due to the potential impacts of red foxes on both prey and competitor species. However, despite it being a common species, there is still surprisingly little knowledge about the temporal and spatial charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 85 publications
0
28
0
Order By: Relevance
“…2), where carrion biomass is also much higher (Hagen 2014). Both these factors might, in addition to higher diversity and stability of other food sources, lead to more stable red fox abundance in forest habitats (Jahren et al 2020). Concurrently, increased activity at baits during winters with low rodent abundance may indicate a diet shift, as predicted by the FRH.…”
Section: Alpine Baitsmentioning
confidence: 99%
“…2), where carrion biomass is also much higher (Hagen 2014). Both these factors might, in addition to higher diversity and stability of other food sources, lead to more stable red fox abundance in forest habitats (Jahren et al 2020). Concurrently, increased activity at baits during winters with low rodent abundance may indicate a diet shift, as predicted by the FRH.…”
Section: Alpine Baitsmentioning
confidence: 99%
“…Carrion can occur in temporal pulses, or be scattered across extensive areas, and can act as a lifesaver for scavengers during the harshest periods. The spatiotemporal availability of carrion will influence the density, distribution, and diversity of scavengers (DeVault et al 2003;Mateo-Tom as et al 2015;Jahren et al 2020), affecting their survival and shifting their diets and feeding behaviour (Sel as & Vik, 2006;Newsome et al 2015). Accidental and intentional supplementary feeding of predators by humans (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Capercaillie populations have been in progressive decline throughout Europe (Storch, 2007;Jahren et al 2016;K€ ammerle et al 2017), beginning earlier in the south of their range and especially sharply in the fragmented and threatened populations of the Iberian Peninsula (Storch, 2007;Gil, G omez-Serrano & L opez-L opez, 2020). This decline has been attributed to low reproductive success and recruitment due to variety factors, such as climate change, habitat loss and fragmentation, human disturbance and the impact of generalist predators (Storch, 2007;Moreno-Opo et al 2015;Jahren et al 2016Jahren et al , 2020K€ ammerle et al 2017). It has been suggested that the increase in generalist predator populations, such as the red fox and marten species, has been favoured by the increase in agricultural areas and human settlements, the lack of apex-predators, and especially by the increase in carrion from wild ungulates as well as conservation policies protecting mesocarnivores (Kurki et al 1998;Sel as & Vik, 2006;Jahren et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, the red fox and martens were responsible for more than one half of destroyed artificial nests (61%) which is in line with predation on real black grouse nests in Norway [ 77 ]. The increasing predation risk on forest grouse populations is more pronounced in recent decades due to increasing population trends of generalist mesocarnivores or corvid species, especially caused by land-use changes or legal protection [ 8 , 78 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%